Moderation of External Pressure on the Effect of Budget Participation on Budget Gaps - Siregar, Siti Aisyah; Nainggolan, Edisah Putra; Fadhila, Novi (AIBPM Publisher, 2023)
This study aims to analyze the Moderation of External Pressure on the effect of Budget Participation on Budgetary Gaps in local governments in Deli Serdang Regency. The population in this study were local government officials who are members of the Regional Work Unit (SKPD) in Deli Serdang Regency, the sample selected was 100 respondents. This study used a quantitative approach, data were analyzed using the Partial Least Square (PLS) analysis technique. The results of the study show that external pressure mediates the effect of budgetary participation on budgetary gaps in local governments in the Deli Serdang district.